The Imposition of Form : Studies in Narrative Representation and Knowledge - Brodsky, Claudia, 1955- (Book collections on Project MUSE., 1987)
Claudia Brodsky skillfully combines close readings of narrative works by Goethe, Austen, Balzac, Stendhal, Melville, and Proust with a detailed analysis of the relation between Kant's critical epistemology and narrative theory. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions.